Mechanical thrombectomy as an alternative reperfusion therapy in acute ischaemic stroke associated with recent late presentation of ST elevation myocardial infarction - Hashim Embong; Samshiyah AS; Azuan NI (Pusat Perubatan Universiti Kebangsaan Malaysia, 2018)
Concomitant recent myocardial infarction (MI) in patients presenting with acute ischaemic stroke (AIS) is considered a relative contraindication for thrombolysis. Mechanical thrombectomy is recognised as an alternative recanalisation therapy to avoid risk of haemorrrhagic complications. We report a 77-year-old patient who previously had recent admission for late presentation ST elevation myocardial infarction (STEMI) and currently presented with right-sided hemiplegia, dysphasia and reduced level of consciousness at 30 minutes from the onset. An urgent cerebralangiography showed total occlusion of the left middle cerebral artery (MCA). Successful mechanical thrombectomy was performed instead of administration of intravenous (IV) thrombolysis with excellent neurological recovery. This case report highlights the importance of patient transfer to a more comprehensive stroke center in the management strategies of the AIS.